Supersymmetric Quantum Mechanics and Partially Solvable Potential - Drigo Filho, E. [UNESP]; Ricotta, R. M. [UNESP] (My University, 1998)
Supersymmetric quantum mechanics can be used to obtain the spectrum and eigenstates of one-dimensional Hamiltonians. It is particularly useful when applied to partially solvable potentials because a superalgebra allows us to compute the spectrum state by state. Some solutions for the truncated Coulomb potential, an asymptotically linear potential, and a nonpolynomial potential are shown to exemplify the method.